Determinant Factors for Managing Sustainable Waste Bank in Bantul Urban Areas - Bambang Suwerda; Su Rito Handoyo; Andri Kurniawan (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
The management of waste bank in urban areas of Bantul has been running for ten years, andmany are currently inactive. This study examines the intention of managing a sustainable wastebank in the urban area of Bantul. The aim of this study is to determine the factors associatedwith intention sustainable management of waste banks in the urban area of Bantul Regency. Theresearch sample was a waste saver in the waste bank of the urban area of Bantul Regency. Thedata were analyzed by path analysis. The results of the study show that there is a significant relationship between the role of the government and the Independent Waste Management Network(JPSM) with the participation of community in waste bank. Knowledge, participation, the role ofthe government and JPSM have a significant relationship with the intention of the community inthe waste bank. This study helps understand the strength of the relative relationship of the determinants of intention to manage a sustainable waste bank. The strength of the biggest relationship is between the role of government and JPSM with intentions, followed by role relationshipswith participation, then between participation and intention, and the weakest is the relationshipbetween knowledge and intention